Surgical Morbidity and Lung Function Changes After Laser–Assisted Pulmonary Metastasectomy: A Prospective Bicentric Study - Hassan, Mohamed; Graeter, Thomas; Dietrich, Irene; Kemna, Lars Johann; Passlick, Bernward; Schmid, Severin (Frontiers in Surgery, 2021)
Objective: The surgical resection of pulmonary metastases is associated with a survival benefit in selected patients. The use of laser devices for pulmonary metastasectomy (PM) is believed to facilitate the complete resection of metastases while preserving a maximum of healthy parenchyma. This is a prospective study to evaluate surgical outcome including the changes of lung function after laser–assisted surgery (LAS). Methods: A total of 77 operations in 61 patients in which PM was carried out in a curative intent were analyzed. A 1.320 nm diode-pumped Nd: YAG-Laser was used for resection of the metastases. Surgical and clinical data were collected using a standardized form and postoperative lung function changes 3 and 6 months after surgery were assessed using whole body plethysmography and diffusion capacity for carbon monoxide (DLCO). Size and distance of metastases to the pleural surface were measured radiologically. Results: A median of 2 metastases were resected per operation (range 1-13). The median duration of postoperative air leak was 1 day (range 0-11). LAS associated postoperative minor and major complications were observed in 4 (5%) cases and 1 (1%) case respectively; there were no mortalities. The analysis of perioperative lung function showed that mean VC 3 months after surgery was reduced by 11 %, FEV1 by 11% and median DLCO by 11% (all p<0.0001). There was almost no recovery of lung function between 3 and 6 months in the whole cohort. Patients with 2 or less metastases showed a recovery of lung function after 3 months regarding DLCO (p=0.003). Decline of DLCO in the whole cohort correlated with the number of resected metastases at 3 months (r=0.45, p=0.006) and at 6 months (r=0.42, p=0.02) as well as depth of metastases in the parenchyma at 6 months (r=0.48, p=0.001). Conclusions: LAS is a safe and effective method for PM even for higher numbers of metastases, with short duration of postoperative air leak and little morbidity. Number and depth, but not size of metastases affect lung function changes after resection.